Targeting WEE1 Kinase in Gynecological Malignancies - Zhang W; Li Q; Yin R (Dove Medical Press, 2024)
Wenhao Zhang,1,2 Qingli Li,1,2,* Rutie Yin1,2,* 1Department of Obstetrics and Gynecology, West China Second University Hospital, Sichuan University, Chengdu, People's Republic of China; 2Key Laboratory of Birth Defects and Related Diseases of Women and Children (Sichuan University), Ministry of Education, Chengdu, People's Republic of China*These authors contributed equally to this workCorrespondence: Rutie Yin, Department of Obstetrics and Gynecology, West China Second University Hospital, Sichuan University, Chengdu, 610041, People's Republic of China, Email yrtt2013@163.com Qingli Li, Key Laboratory of Birth Defects and Related Diseases of Women and Children (Sichuan University), Ministry of Education, Chengdu, People's Republic of China, Email liqingli73@163.comAbstract: WEE1 kinase is involved in the G2/M cell cycle checkpoint control and DNA damage repair. A functional G2/M checkpoint is crucial for DNA repair in cancer cells with p53 mutations since they lack a functional G1/S checkpoint. Targeted inhibition of WEE1 kinase may cause tumor cell apoptosis, primarily, in the p53-deficient tumor, via bypassing the G2/M checkpoint without properly repairing DNA damage, resulting in genome instability and chromosomal deletion. This review aims to provide a comprehensive overview of the biological role of WEE1 kinase and the potential of WEE1 inhibitor (WEE1i) for treating gynecological malignancies. We conducted a thorough literature search from 2001 to September 2023 in prominent databases such as PubMed, Scopus, and Cochrane, utilizing appropriate keywords of WEE1i and gynecologic oncology. WEE1i has been shown to inhibit tumor activity and enhance the sensitivity of chemotherapy or radiotherapy in preclinical models, particularly in p53-mutated gynecologic cancer models, although not exclusively. Recently, WEE1i alone or combined with genotoxic agents has confirmed its efficacy and safety in Phase I/II gynecological malignancies clinical trials. Furthermore, it has become increasingly clear that other inhibitors of DNA damage pathways show synthetic lethality with WEE1i, and WEE1 modulates therapeutic immune responses, providing a rationale for the combination of WEE1i and immune checkpoint blockade. In this review, we summarize the biological function of WEE1 kinase, development of WEE1i, and outline the preclinical and clinical data available on the investigation of WEE1i for treating gynecologic malignancies.Keywords: WEE1 inhibitor, cell cycle, gynecological malignancies, adavosertib, clinical trials